Adenoma de células basales de parótida. Caso clínico y revisión de la literatura - Herrera L., Josefina; Cabané T., Patricio; Morales H., Claudia (Revista Hospital Clínico Universidad de Chile, 2014)
Objetive: To report a case of basal cell adenoma in an adult patient. Introduction: The basal cell adenoma is a rare tumor, it represents the 1-2% of the major salivary gland tumors. It has a low malignancy rate and a good prognosis, but it has high recurrency. It is tipically presented during the fifth decade of life, and its usually as a firm and movable mass of slow growth. Case Report: A 58-year-old man with a left parotid tumor of 4 months of evolution, with no other symptoms. A total parotidectomy is performed without any incidents, or sequels. The deferred biopsy showed a basal cell adenoma. Discussion: The histopathological analysis is essential for the differential diagnosis with malignant tumors. As there are case reports that shows malignancy of the basal cell adeno